Response of castor (Ricinus communis L.) to crop geometry and potassium on growth, yield attributes and yields under irrigated condition: RESPONSE OF CASTOR TO CROP GEOMETRY AND POTASSIUM ON YIELD ATTRIBUTES AND YIELDS - P M VAGHASIA; R L DAVARIYA; R N DAKI; K L DOBARIYA (Journal of Oilseeds Research, 2019)
A field experiment was conducted at Main Oilseeds Research Station, Junagadh Agricultural University, Junagadh (Gujarat) during kharif season of 2013-14 to 2015-16. The soil was medium black and clayey in texture. The experiment was laid out in Split Plot Design comprising four levels of plant geometry (G1:150 cm x 90 cm, G2: 150 cm x 60 cm, G3: 120 cm x 90 cm and G4: 120 cm x 60 cm) allotted to main plots and four potassium levels (K1: Control, K2: 20 kg K2O/ha, K3: 40 kg K2O/ha and K4: 50 kg K2O/ha) assigned to sub plots and replicated thrice. The results indicated that castor sown at 150 cm x 60 cm and 120 cm x 60 cm spacing recorded significantly higher plant population, plant height, number of branches, number ofspikes, length of main spike, number of capsules per spike and seed yield in pooled results. While, almost all the growth characters, yield attributes, quality parameters and seed yield were found significantly higher when crop was fertilized with 40 and 50 kg K2O/ha. Interaction effect between crop geometry and potassium levels was significant and crop geometry of 120 cm x 60 cm with potassium application @ 40 kg K2O/ha (G4K3) recorded significantly higher castor seed yield (3714 kg/ha) and net return (`1,01,290/ha) with B:C ratio of 3.81. It was concluded that kharif castor should be sown at 120 cm x 60 cm with an application of potassium @ 40 kg K2O/ha along with recommended dose of nitrogen and phosphorus (120-50 kg NP/ha) for obtaining higher seed yield and net return.